2021
DOI: 10.1016/j.jece.2021.106217
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and CFD evaluation of ozone efficacy against coronavirus and enteric virus contamination on public transport surfaces

Abstract: The limited information about the routes of the transmission of SARS-CoV-2 within the ongoing pandemic scenario mobilized the administration, industry and academy to develop sanitation and disinfection systems for public and private spaces. Ozone has been proposed as an effective disinfection method against enveloped and non-enveloped viruses, including viruses with similar morphology to SARS-CoV-2. Due to this efficacy, numerous gaseous and aqueous phase ozone applications have emerged potentially to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…To a certain extent, studies have found evidence of disinfection having a positive effect in reducing virus transmission, yet more research is needed to establish conclusive evidence. The use of ozone as a disinfectant is studied by Falcó et al (2021) , who find that ozone concentrations must be monitored and kept at specific levels required to eliminate viral infectivity. Moreover, the literature proposes innovative alternatives such as relying on UV-C LEDs and continuous sanitation air systems (CSAs) based on ionizers ( Baldelli et al, 2022 ).…”
Section: Transportation Policies and Mitigations Strategiesmentioning
confidence: 99%
“…To a certain extent, studies have found evidence of disinfection having a positive effect in reducing virus transmission, yet more research is needed to establish conclusive evidence. The use of ozone as a disinfectant is studied by Falcó et al (2021) , who find that ozone concentrations must be monitored and kept at specific levels required to eliminate viral infectivity. Moreover, the literature proposes innovative alternatives such as relying on UV-C LEDs and continuous sanitation air systems (CSAs) based on ionizers ( Baldelli et al, 2022 ).…”
Section: Transportation Policies and Mitigations Strategiesmentioning
confidence: 99%